2010
DOI: 10.2460/ajvr.71.11.1377
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of orally administered DL-α-lipoic acid in dogs

Abstract: Values for pharmacokinetic parameters of orally administered DL-α-lipoic acid may differ significantly when there are changes in dosage, method of administration, and fed status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The maximum serum concentrations of a-LA are within the range of values reported for other species [ 34 ] as is the time to reach peak concentrations of orally administered a-LA in plasma [ 26 , 32 , 59 , 137 ]. The peak concentration of a-LA in plasma is reduced and the time to reach the peak concentration is delayed when a-LA is an ingredient in extruded dog food compared to the peak concentration and the time to reach peak concentration if a-LA is administered orally with or without food, followed by withholding of food for 12 h [ 137 ]. Despite differences, overall, the pharmacokinetic parameters were minimally affected by the fed status of the animal when administered in capsule form.…”
Section: Use Of A-la As a Nutrient Additive In Dog Foodsupporting
confidence: 61%
See 4 more Smart Citations
“…The maximum serum concentrations of a-LA are within the range of values reported for other species [ 34 ] as is the time to reach peak concentrations of orally administered a-LA in plasma [ 26 , 32 , 59 , 137 ]. The peak concentration of a-LA in plasma is reduced and the time to reach the peak concentration is delayed when a-LA is an ingredient in extruded dog food compared to the peak concentration and the time to reach peak concentration if a-LA is administered orally with or without food, followed by withholding of food for 12 h [ 137 ]. Despite differences, overall, the pharmacokinetic parameters were minimally affected by the fed status of the animal when administered in capsule form.…”
Section: Use Of A-la As a Nutrient Additive In Dog Foodsupporting
confidence: 61%
“…A pharmacokinetic study of orally administered a-LA in dogs showed that pharmacokinetic parameters of a-LA were influenced by dose and the mode of administration [ 137 ]. Absorption of a-LA is reduced when it is used as an ingredient in extruded dog food compared to its absorption of a comparable dose of orally administered a-LA in the form of a capsule, given with or without food [ 137 ]. However, the concentrations of a-LA in plasma increased in proportion with the dose, regardless of its administration orally in a capsule form or as an ingredient in dog food [ 137 ].…”
Section: Use Of A-la As a Nutrient Additive In Dog Foodmentioning
confidence: 99%
See 3 more Smart Citations